2019
DOI: 10.1097/phh.0000000000000768
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Record Implementation Findings at a Large, Suburban Health and Human Services Department

Abstract: Electronic health records can benefit public health practices in many ways; however, public health departments will face significant challenges incorporating EHRs, which are typically designed for non-public health settings, into the public health workflow. Electronic health record implementation recommendations for health departments are provided. When implementing an EHR in a public health setting, health departments should provide extensive preimplementation training opportunities, including EHR training ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
4
0
7
Order By: Relevance
“…The framework has been used for diverse interventions in inpatient, clinic and community settings. A systematic review in 2016 identified 26 empirical studies using the CFIR, [62] and there are numerous studies published since then [43,[63][64][65][66][67][68][69][70][71]. However, only two previous studies occurred in a high acuity inpatient setting (adult acute care units) [63,70] and no prior studies include the NICU setting.…”
Section: Preparing Nicus To Adapt H-hope As the Standard Of Carementioning
confidence: 99%
“…The framework has been used for diverse interventions in inpatient, clinic and community settings. A systematic review in 2016 identified 26 empirical studies using the CFIR, [62] and there are numerous studies published since then [43,[63][64][65][66][67][68][69][70][71]. However, only two previous studies occurred in a high acuity inpatient setting (adult acute care units) [63,70] and no prior studies include the NICU setting.…”
Section: Preparing Nicus To Adapt H-hope As the Standard Of Carementioning
confidence: 99%
“…Na amostra desta pesquisa, observou-se, em três estudos, a aplicação do questionário apenas de forma online, por meio de link, via e-mail ou outras formas de comunicação, sem a necessidade de material impresso (Abramson et al, 2012;Crowley et al, 2019;Hadji et al, 2016). Outras três pesquisas utilizaram métodos online e/ou enviaram o questionário impresso via correio (Adler-Milstein, DesRoches, et al, 2014;Adler-Milstein et al, 2015.…”
Section: Composição Do Instrumento De Coletaunclassified
“…Na busca do sucesso empresarial, medir desempenho de sistemas de informação pode ser considerado uma das principais estratégias, tornando-se, desse modo, um diferencial competitivo. Não muito divergente, quando essa mesma preocupação é direcionada para organizações na área da saúde, é essencial que esses sistemas apresentem um excelente funcionamento, capaz de organizar e manipular grandes quantidades de informação, em prol do alcance dos objetivos organizacionais (Crowley et al, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The framework has been used for diverse interventions in inpatient, clinic and community settings. A systematic review in 2016 identi ed 26 empirical studies using the CFIR, [61] and there are numerous studies published since then [42,[62][63][64][65][66][67][68][69][70]. However, only two previous studies occurred in a high acuity inpatient setting (adult acute care units) [62,69] and no prior studies include the NICU setting.…”
Section: Preparing Nicus To Adapt H-hope As the Standard Of Carementioning
confidence: 99%